The problem of modern literary criticism between tradition and renewal: The theory of receive and interpretation - Badawy, Abeer Abdul- Sadiq Muhammad (Journal of Humanities & Social Sciences, 2021)
Identifying the concept of a text, its analysis and interpretation are of great importance in literary critical studies among western and Arab scientists and researchers of all time. This theory was rooted in Arabic Rhetoric and interpretation of Holy Qura’n before the existence of modern linguistics and western theories. Recently, the text- reader relation has been developed in light of these grounded theories assuring that the base of the literary work in the interaction between the text construction and its readers. This interaction is mainly attained from the real interactivity between them both through receive theory as the recipient gets involved expecting something. The most important point is that reading should be productive by adding new dimensions and unlimited to the barriers of the text. The problems of reading and interpretation revolve around two main axes; first, the literary work and nature of the text, second, the interpretation and understanding of the text. Then, the issue is related to the subjectivity and objectivity of the text, and the degree of the reader’s understanding and interpretation of it. So, it is a harmonized system that collects the elements of creativity; the author, the reader and the text when relating reading process to receive mechanics and interpretation. The current results confirmed that Arabic Rhetoric and critical literature have significant roles in the treatment of the text and its components.